LIFE AND ITS VALUE: PSYCHOLOGICAL PERSPECTIVES - Thadavanal, Jose (Journal of Dharma, 1996)
Most observers of human nature recognize an inner tension in man - the tension between the good and the evil in him, the tension between man's striving for the sublime, on the one hand, and the animal impulses in him that are thought to be part of his evolutionary heritage, on the other. St. Paul, speaking from his own experience, referred to this puzzling phenomenon in his characteristic spiritual language.